Comparative Study of Third Eye for Visually Challenged with Alternate Solution - P, Nandhini; M, Sathanika; J, Sarulatha; M, Vignesh; R, Yougan Bhalaji S (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Deficiency that cannot be reformed in the eye is the blindness. This research aims to investigate the potential benefits and limitations of incorporating electronic sensors and assistive technologies into traditional blind sticks to create a smart blind stick. A smart blind stick is a wearable device that provides additional functionality and features to help visually impaired individuals navigate their surroundings more safely and independently. A smart stick is planned with impediment identification module and object detection. A stick is made in a way that it can sense obstacles and staircases by using sensors. It also intimates the presence of water and manhole. Global Positioning System (GPS) is used to locate the visually impaired person as it is incorporated in the stick used. Global system for Mobile Communication (GSM) is also used. Status of the blind person will be notified to the guardian with the image and location. Overall, this research contributes to the development and improvement of assistive technologies for visually impaired individuals and provide insights for researchers, healthcare professionals, and policymakers on how to better support individuals with visual impairments.